A Model of the Interactions between Banking Crises and Currency Crises - Bleaney, Michael; Bougheas, Spiros; Skamnelos, Ilias (2012)
A second-generation model of currency crises is combined with a standard banking model. In a pegged exchange rate regime, after funds have been committed to the banks, news arrives about the quality of the banks' assets and about the exchange rate fundamentals. A run on the banks may cause a currency crisis, or vice versa. There are multiple equilibria (with either twin crises or no crisis), depending on depositors' expectations of other depositors' actions. Suspension of deposit convertibility can prevent a speculative attack on the currency, but last resort lending to solvent banks can induce one.